eaching Synaptic Transmission Using Primary Literature: A Skills-Focused Pedagogical Approach - Payne, Andrew J; Bills, Kyle B; Steffensen, Scott C (Journal of undergraduate neuroscience education, 2023)
Neuroscience is a burgeoning and intensive undergraduate major at many institutions of higher education. However, several areas in neuroscience education need further development. One such needed development is an increased focus on the procurement of career-relevant skills in addition to the traditional acquisition of subject knowledge. Skill development is particularly challenging in neuroscience education as the subject’s interdisciplinary nature provides an atypically broad range of potential careers for graduates. Skills common to many careers in neuroscience include the ability to understand and analyze quantitative data and to draw conclusions based on those analyses. Here is presented an active learning pedagogical approach involving the analysis of seminal articles in the primary scientific literature to provide practice in analyzing data and drawing conclusions from those data while at the same time learning the fundamental tenets of synaptic transmission. Articles were selected that highlight principles such as the role of Ca2+ in synaptic release, exocytosis, quantal release, and synaptic delay. Figures from these articles that can readily be used to teach these principles were selected, and questions that can help to guide students’ analysis of the data are also suggested. Activities like this are needed in greater numbers to facilitate the process of helping students gain skills relevant to a productive career in neuroscience.